Manajemen Pendidikan Tinggi Islam dalam Spektrum Blue Ocean Strategy - Mardia Mardia (Universitas Islam Negeri Mataram, 2011)
The Islamic higher educations are undergoing important changes involving the development of missions and reorganization of management, with implications for their quality education in the midst of complexity. The main study of this article highlights the importance of governance quality in Islamic higher education in the face of complexity from the perspective of Blue Ocean Strategy. It can be concluded that to win in the future, Islamic higher educations must stop competing each other. The only way to beat the competition is to stop trying to beat the competition. Blue Ocean Strategy to be one of the alternatives in the management of educational institutions to create distinctive adavantage and competitiveness based graduates.